An investigation of the strain dependence of dynamic precipitation in an Al-Zn-Mg-Cu alloy. (15th July 2017) - Couturier, L.; Deschamps, A.; De Geuser, F.; Fazeli, F.; Poole, W.J.
Abstract: The use of high strength Al-Zn-Mg-Cu alloys in automotive components is restricted by their low formability. Warm forming in the under-aged state improves formability, but induces a strain-dependent microstructure evolution due to dynamic precipitation. We present a new methodology to quantitatively evaluate the dynamic precipitation strain dependence which is applicable to strain rates relevant to forming. The plastic strain is varied using a tapered tensile sample and the precipitation state is measured in terms of size and volume fraction using spatially resolved small-angle X-ray scattering, showing its evolution during straining is dependent on the imposed strain level and rate. Graphical abstract: